Linear-time geometric algorithm for evaluating Bézier curves. (January 2020) - Woźny, Paweł; Chudy, Filip
Abstract: A new algorithm for computing a point on a polynomial or rational curve in Bézier form is proposed. The method has a geometric interpretation and uses only convex combinations of control points. The new algorithm's computational complexity is linear with respect to the number of control points and its memory complexity is O ( 1 ) . Some remarks on similar methods for surfaces in rectangular and triangular Bézier form are also given. Highlights: A new algorithm for computing a point on a polynomial or rational curve in Bézier form is proposed. The method has a geometric interpretation and uses only convex combinations of control points. The new algorithm's computational complexity is linear with respect to the number of control points and its memory complexity is O ( 1 ) . Some remarks on similar methods for surfaces in rectangular and triangular Bézier are also given.